The Effect of Electronic Marketing on the Quality of Tourism Services in Libya - Dr. Mohamed Othman EI-fitouri (International Journal of Engineering and Management Research, 2021)
The paper investigates enterprises in the Libyan tourism industry and their perception of the role of e-marketing in developing the industry. It considers enterprises that do not apply e- marketing, the problems they face and the benefits they would gain from an e-marketing programme. In relation to this the importance of e-marketing and the extent to which theory is followed is examined. The paper explores what should be done to develop e-marketing for tourist enterprises and how to implement strategic plans for the industry to increase its market share to enable it to compete in the international market place. The tourism industry is important to Libya’s economy and greater consideration should be given to its development and, in particular, to e-marketing. This is especially the case for small and medium-sized tourism enterprises (SMTEs) since most industrial sectors depend on these composing 50% privately owned and the rest full or part government owned.